Using geodata and geolocation in the social sciences mapping our connected world - Abernathy, David (London SAGE Publications Ltd, 2017)
Using Geodata and Geolocation in the Social Sciences: Mapping our Connected World provides an engaging and accessible introduction to the Geoweb with clear, step-by-step guides for: . Capturing Geodata from sources including GPS, sensor networks and Twitter . Visualizing Geodata using programmes including QGIS, GRASS and R Featuring colour images, practical exercises and a companion website packed with resources, this book is the perfect guide for students and teachers looking to incorporate location-based data into their social science research.
Keywords: Geodatabases -- Social aspects; Geography -- Statistical methods; Social sciences -- Geographic information systems; Geography -- Statistical methods -- Data processing